Multi-channel ground-penetrating radar to explore spatial variations in thaw depth and moisture content in the active layer of a permafrost site - Wollschläger, Ute; Gerhards, Holger; Yu, Q.; Roth, Kurt (The Cryosphere, 2010)
Multi-channel ground-penetrating radar (GPR) was applied at a permafrost site on the Tibetan Plateau to investigate the influence of surface properties and soil texture on the late-summer thaw depth and average soil moisture content of the active layer. Measurements were conducted on an approximately 85 × 60 m2 sized area with surface and soil textural properties that ranged from medium to coarse textured bare soil to finer textured, sparsely vegetated areas covered with fine, wind blown sand, and it included the bed of a gravel road. The survey allowed a clear differentiation of the various units. It showed (i) a shallow thaw depth and low average soil moisture content below the sand-covered, vegetated area, (ii) an intermediate thaw depth and high average soil moisture content along the gravel road, and (iii) an intermediate to deep thaw depth and low to intermediate average soil moisture content in the bare soil terrain. From our measurements, we found hypotheses for the permafrost processes at this site leading to the observed late-summer thaw depth and soil moisture conditions. The study clearly indicates the complicated interactions between surface and subsurface state variables and processes in this environment. Multi-channel GPR is an operational technology to efficiently study such a system at scales varying from a few meters to a few kilometers.
Gesehen am 25.04.2024